Income Taxation, Government Expenditure, and Long-Run Stochastic Growth - Christiane Clemens (Universität Hannover, Wirtschaftswissenschaftliche Fakultät, 1999)
This paper employs a stochastic endogenous growth model with productive government expenditure to analyze the macroeconomic effects of income taxation. We demonstrate that in the presence of capital and income risk the impact of taxation on consumption choice as well as on economic growth is ambiguous as it affects the mean as well as the variance of disposable income. We observe that the effects of taxation crucially depend on the degree of risk aversion and on the capital income share. Nevertheless, it is possible to solve for welfare maximizing policies. Compared to the deterministic setting, for the optimal policy design additional conditions have to be met.
Keywords: D8; D9; E62; O4; 330; Endogenous Growth; Taxation; Uncertainty